2021
DOI: 10.1021/acssynbio.1c00331
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Heavy Metal Sensors Based on Transcription Factors and Cell-Free Expression Systems

Abstract: Many bacterial mechanisms for highly specific and sensitive detection of heavy metals and other hazards have been reengineered to serve as sensors. In some cases, these sensors have been implemented in cell-free expression systems, enabling easier design optimization and deployment in low-resource settings through lyophilization. Here, we apply the advantages of cell-free expression systems to optimize sensors based on three separate bacterial response mechanisms for arsenic, cadmium, and mercury. We achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…Since TFs corresponding to heavy metals have been identified, the cell-free biosensors for detecting heavy metals have been reported by many research groups [ 72 , 73 , 74 ]. Recently, Beabout et al reported heavy metal biosensors based on cell-free expression systems.…”
Section: Transcription Factor-based Biosensorsmentioning
confidence: 99%
“…Since TFs corresponding to heavy metals have been identified, the cell-free biosensors for detecting heavy metals have been reported by many research groups [ 72 , 73 , 74 ]. Recently, Beabout et al reported heavy metal biosensors based on cell-free expression systems.…”
Section: Transcription Factor-based Biosensorsmentioning
confidence: 99%
“…Advancements in synthetic biology may be a precursor to the future of remediation. These may include specifically engineered microorganisms and synthetic communities and synthetic biomarkers (Beabout et al 2021). As advancements in methods continue to improve accuracy and resolution, so do the libraries of known analytes.…”
Section: Future Directions For Omicsmentioning
confidence: 99%
“…Also, cell-free systems do not risk the release of genetically modified organisms into nature, as simple metabolic pathways do not pose the same environmental threat as engineered microbes [23,54]. Without homeostatic concerns, cell-free biosensors can also operate in a diverse range of environments that would otherwise be toxic for cell-based systems, and cell-free systems can achieve higher sensitivities to toxic analytes because of the systems' ability to withstand higher concentrations of toxins [23,54]. Finally, cell-free systems are also not subject to concerns about evolutionary change altering sensor function [23].…”
Section: Cell-free Biosensingmentioning
confidence: 99%
“…One possible avenue of detection is the utilization of transcription factors for the detection of target ligands. Transcription factor detection involves the expression of a reporter molecule such as green fluorescent protein (GFP) in the presence of a target analyte, where the presence of the analyte will cause an inhibitory molecule, which is bound to the operator controlling the expression of the reporter molecule, to break off, allowing for the expression of the reporter [54,56,57]. Another possible detection method utilizes riboswitches, which are RNA structures that regulate gene expression through the binding of certain metabolites [23].…”
Section: Cell-free Biosensingmentioning
confidence: 99%